Empirical analysis on the implementation of green supply chain management (GSCM) in the construction industry - Mahmud, Fatimah; Rahamaddulla, Syed Radzi; Maarof, Mohd Ghazali; Mohamad, Fazeeda; Safiynaz, Omar; Zarith Sufia, Azlan (2018)
Since the construction industry has been identified to be one of the major contributors to the environmental pollution, innovations are made recently which drive to the emergence of sustainability concept. Converging sustainability with the core business functions such as supply, operations, and purchasing strategies has led to a new interdisciplinary field called the green supply chain management (GSCM). GSCM can be explained as the way in which the activities of supply chain management and industrial purchasing being considered in the context of the environment. While other regions have adopted GSCM as their core business strategies, the Malaysian construction industry is still slowly warming up to adapt the concept. Therefore, this research is conducted with the aim to establish the level of adoption of GSCM in the Malaysian construction industry. In order to achieve the aim, three objectives had been highlighted including (1) to investigate the awareness level of industry players towards GSCM concept in the construction industry, (2) to identify the current implementations of GSCM in the Malaysian construction industry, and (3) to analyse the challenges faced by the players in the Malaysian construction industry in adopting green supply chain practice. The research methodology adopted includes questionnaire survey and semi-structured interview in order to gain the primary data. While for secondary data, comprehensive literature review was conducted. Data collected were scrutinized using SPSS software and content analysis and presented in various forms of table and figure. From the analysis conducted, it can be summarized that the level of adoption of GSCM in the Malaysian construction industry was still at the development phase. There were still many industry players who are not highly aware on the concept and definitions of GSCM even though they did aware on the environmental impacts of construction supply chain. Besides, the implementation of GSCM in the Malaysian construction industry was not as a whole and on several supply chain phase only. The involvement mainly to those who involved with green projects. Various challenges that hinder the players from adopting the concept are being identified. Some examples of the challenges include leadership and commitment from top management, lack of government support and regulations, and fear of failure. Apart from that, several recommendations were derived from the analysis and are expected to help improve the implementation of GSCM in the Malaysian construction industry. In relation to the findings, there is an opportunity for research to be continued in order to contribute more in sharing ideas and solutions towards these issues. In-depth study can be done for each of the initiatives or approaches under GSCM implementation, antecedents that can motivate organisations to adopt GSCM and the relationship between ISO certified organisations with the implementation of GSCM. It is hoped that, the research information will be useful in promoting GSCM amongst the Malaysian construction industry players.